(untitled) (BISTUA Revista de la Facultad de Ciencias Básicas, 2024)
Impacts of mining and agriculture have turned mercury (Hg), methylmercury (MeHg), zinc (Zn), cadmium (Cd), lead (Pb) and copper (Cu) into common pollutants in the fish and ecosystem compartments of Colombian wetlands. For this reason, in this study we evaluated concentrations of these metals in Hoplias malabaricus muscle, and determining their variations according 5 cooking methods (Smoked, Fried, Stew, Viuda and Salpicón). The concentrations were determined by thermal decomposition, amalgamation and atomic absorption spectroscopy (EPA-7473) (Hg-MeHg), atomic absorption spectroscopy with flame (FLAAS) (EPA-7000B) (Zn-Cu) and atomic absorption spectroscopy in graphite furnace (GFAAS) (EPA-7010) (Pb-Cd).We found Zn was the metal most accumulated in this tissue, likewise Cd (Fried, Viuda, Smoked and Salpicón) and Pb (Salpicón) exceeded maximum permissible limits (EU, 2018) and FAO (1992) for mean concentrations in fish muscle for human consumption. Similarly significant differences (p<0.05) in mean concentrations of Cd and Pb in muscle cooked with Smoked in Salpicón methods were determined respect to the rest. Risk indicators (DID, HQ and HI) for health assessment of the population by consumption of Hoplias malabaricus showed La Mojana habitants are exposed to high risk level, mainly due consumption of this species cooked with Salpicón method.